Hydrogeological and geotechnical issues associated with water accumulation in the historic shafts of the Wieliczka Salt Mine: the Górsko Shaft case Języki publikacji PL - d’OBYRN, Kajetan; PRZYBYŁO, Jerzy (Geology, Geophysics and Environment, 2012)
The Górsko Shaft was excavated to the depth of Level I in the first half of the seventeenth century, and was probably completed in 1622. in the nineteenth century, the shaft was extended. in 1954, the Górsko Shaft was filled up to a depth of approximately 6 meters below the ground. Infl ows out of the Górsko Shaft were first observed in the shaft bottom and in Fryderyk August chamber. Through suffusion and leaching salt formations, migratory waters caused soil settling and structural damage to the shaft top building. In February 2011, a technical design for the sealing of the Górsko Shaft was developed, which calls for cementing work and the elimination of surface water infl ow through the shaft into the mine workings. Engineering work related to the restriction of the flow of water into the Górsko Shaft began in December 2011.